Potential Relationship between Passive Plantar Flexor Stiffness and Running Performance - Ueno, Hiromasa; Suga, Tadashi; Takao, Kenji; Tanaka, Takahiro; Misaki, Jun; Miyake, Yuto; Nagano, Akinori; Isaka, Tadao (International Journal of Sports Medicine, 2018)
The present study aimed to determine the relationship between passive stiffness of the plantar flexors and running performance in endurance runners. Forty-eight well-trained male endurance runners and 24 untrained male control subjects participated in this study. Plantar flexor stiffness during passive dorsiflexion was calculated from the slope of the linear portion of the torque-angle curve. Of the endurance runners included in the present study, running economy in 28 endurance runners was evaluated by measuring energy cost during three 4-min trials (14, 16, and 18 km/h) of submaximal treadmill running. Passive stiffness of the plantar flexors was significantly higher in endurance runners than in untrained subjects. Moreover, passive plantar flexor stiffness in endurance runners was significantly correlated with a personal best 5000-m race time. Furthermore, passive plantar flexor stiffness in endurance runners was significantly correlated with energy cost during submaximal running at 16 km/h and 18 km/h, and a trend towards such significance was observed at 14 km/h. The present findings suggest that stiffer plantar flexors may help achieve better running performance, with greater running economy, in endurance runners. Therefore, in the clinical setting, passive stiffness of the plantar flexors may be a potential parameter for assessing running performance.
Keywords: Running economy; oxygen consumption; range of motion; muscle-tendon complex; ankle joint; tendon stiffness